The Influence of Public Service Motivation (PSM) on Public Sector Innovation (PSI) at the Dinas Kependudukan dan Catatan Sipil (Disdukcapil) Kota Bandung - Kristian Widya Wicaksono; Thesalonica Angeline Lesmana (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2022)
Public Service Motivation (PSM) research continues to advance. Based on recommendations from prior research, this study was conducted to determine the strength of the relationship between PSM and Public Sector Innovation (PSI). The researchers decided to conduct their research at the Dinas Kependudukan dan Catatan Sipil (Disdukcapil) Kota Bandung. It is a result of the symptom of a problem in Disdukcapil, which demonstrates that Aparatur Sipil Negara (ASN) treats service users differently based on collusion, and they receive undue benefits from service users. Against this backdrop, this research aims to determine the strength of the relationship between PSM and PSI in Disdukcapil Kota Bandung. This study employs a quantitative method of the survey type. All ASNs in Disdukcapil Kota Bandung, a total of 91 individuals, were recruited to become the respondents in this study using a saturated sampling technique. Questionnaires were used to collect data. The data was then analyzed using the linear regression, t-test, and spearman rank formula to determine the strength of PSM's influence on PSI. The findings revealed that there was a correlation between PSM and PSI. The relationship exists at robust coefficient intervals. However, the effect of PSM on PSI was only 32.3%, with the remainder influenced by other variables not investigated in this study.